SYNTHESIS METHODS AND PROPERTIES OF METALLIC NANOSTRUCTURES - Kalandarov Farhod Astonaqulovich (European Science Publishing, 2025)
It is now well known that the size and shape of metallic nanostructures can significantly alter their properties. The large surface area to volume ratio of metallic nanostructures is the reason for a number of unique applications, especially in catalysis. Metallic nanostructures possessing LSPR in the visible wavelength range are typically metals with a negative real and small positive imaginary dielectric permittivity, such as gold, silver, and copper. Interest in the rational synthesis of metallic nanostructures with controlled sizes and morphology is based not only on their aesthetic appeal.
Keywords: Metal nanostructure, morphology, Au and Ag nanostructures, LSPR, photochemical, thermal decomposition.